Accumulation of Arsenic and Fluoride in Lichen Pyxine cocoes (Sw.) Nyl., Growing in the Vicinity of Coal-based Thermal Power Plant at Raebareli, India - S. Nayaka, Rajesh Bajpai, D. K. Upreti* (Journal of Experimental Sciences, 2010)
<div style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: windowtext 1pt solid; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 0in; BORDER-LEFT: medium none; PADDING-TOP: 1pt; BORDER-BOTTOM: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt"><p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 0in; MARGIN: 6pt 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-padding-alt: 1.0pt 0in 0in 0in; mso-border-top-alt: solid windowtext .5pt">ABSTRACT: Levels of arsenic (As) and fluoride (F) were determined in an epiphytic lichen Pyxine cocoes (Sw.) Nyl., collected from the vicinity of coal based thermal power plant of Raebareli, India. Both the elements are abundant in lichen thallus, while their substratum contained negligible amount. The As ranged between 8.9Â±0.7 to 77.3Â±2.0 Âµg g-1 dry weight in thallus and 1.0Â±0.0 to 9.7Â±0.2 Âµg g-1 dry weight in substratum; whereas F ranged between 9.3Â±0.52 to 105.8Â±2.3 Âµg g-1 dry weight in thallus however, it not detected in the substratum. The quantities of As in thallus increased with decreasing distance from the power plant, but F showed an opposite trend. The distribution of As and F around the power plant showed positive correlation with distance in all directions with better dispersion in western side as indicated by the concentration coefficient (R2). The F accumulaiton patterns in lichens clearly indicate that theÂ coal burning in power plant is the major contributor, and has its maximum levels on the down wind side. The analysis of variance and LSD indiacted that the As, F concentrations among lichen thallus is significant at p< 0.01% level. <p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 0in; MARGIN: 6pt 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-padding-alt: 1.0pt 0in 0in 0in; mso-border-top-alt: solid windowtext .5pt">Â Key words: Bioaccumulation, Arsenic, Fluoride, Lichen, Thermal Power Plant Please Cite This Article As: R. Bajpai et al. 2010. Accumulation of Arsenic and Fluoride in Lichen Pyxine cocoes (Sw.) Nyl., Growing in the Vicinity of Coal-based Thermal Power Plant at Raebareli, India. J. Exp. Sci. 1(4):34-37.